Introduction to Tuḥfah al-Ikhwān fī Khaṣāiṣ al-Fityān and the Concept of Its Fundamental Theme On Futuwwah (Chivalry) - Hashtroodi, Fatemeh (Jurnal Usuluddin, 2012)
Tuḥfah al-Ikhwān Fī KhaṣāIṣ al-Fityān is one of the valuable collections of treatises on chivalry, which encompasses spiritual nature. It is written by ‘Abd al-Razzāq Kashānī in fourteenth century. The remarkable point about this treatise is that it was written in Arabic and Persian by the same author. On the other hand, it diffuses ethical issues, which even goes beyond ethic and addresses the different stage of human spirituality. It submits a profound understanding of the meaning of chivalry, further than ethic and provides the method of attaining chivalry. According to Kāshānī, chivalry take shape in the vicinity of selfhood, while considers the borderline of sociability.